1984
DOI: 10.1177/002246698401800408
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the Children Special Education Should Serve and How Many Children Are There?

Abstract: Determining the number of school-age children who need special education has been a persistent problem for many years. The crux of the problem is to clearly identify the population of children who are to be served by special education. A specific concern is OSE's use of the 12.035% prevalence figure for handicapping conditions and the implication that states not serving this percentage of school-age children are not in compliance with the law. A review of over 10,000 special education students indicates that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…Although I have argued elsewhere (Edgar & Hayden, 1985) that mild MR, LD, and BD students (and Chapter 1 students) are from the same population, these data, along with data from our large study, clearly prove me wrong. Comparing mild MR graduates to LD/BD graduates we found major differences in gender breakdowns (MR 51% male, LD/BD 75% male), in employment rate (MR13%, LD/BD 60%), and in the engagement rate (working or going to 36 school) (MR41 %, LD/BD 84%).…”
Section: Mildly Retarded Studentsmentioning
confidence: 50%
See 1 more Smart Citation
“…Although I have argued elsewhere (Edgar & Hayden, 1985) that mild MR, LD, and BD students (and Chapter 1 students) are from the same population, these data, along with data from our large study, clearly prove me wrong. Comparing mild MR graduates to LD/BD graduates we found major differences in gender breakdowns (MR 51% male, LD/BD 75% male), in employment rate (MR13%, LD/BD 60%), and in the engagement rate (working or going to 36 school) (MR41 %, LD/BD 84%).…”
Section: Mildly Retarded Studentsmentioning
confidence: 50%
“…The more severely involved students tend to be captives of the system-they are placed on school buses, sent to school, returned home, and cycled on and on. However, a sizeable portion (80%) of special education students are mildly handicapped (Edgar& Hayden, 1985), and these students seem to disappear from our secondary schools. They tend to be poor, from ethnic minority families, and they are not adjusting well to adult life in the community.…”
Section: Ldibd Students' Dropout Ratementioning
confidence: 99%
“…Earlier, Reynolds and Balow (1972) suggested that teacher training based on categorical differences in students was an unproductive approach; Smith and Neisworth (1975) argued that categorical training encouraged a search for unique methods and materials that probably did not exist. As Edgar andHayden (1984-1985) indicated, &dquo;the literature is replete with statements that these three groups [ED, LD, EMR] represent essentially the same population&dquo; (p. 533).…”
Section: Discussionmentioning
confidence: 99%
“…Mainstream classrooms have been strongly recommended for years as the preferred placement for many exceptional children (Edgar & Hayden, 1982;Lilly, 1982;Sontag, 1982). Stainback and Stainback (1984) have called for an outright merger of special and regular education into one unified system within school districts.…”
mentioning
confidence: 99%